Liver Anesthesiology and Critical Care Medicine (Springer International Publishing, 2018)
Providing anesthesiology for liver surgery and especially liver transplantation is highly complex and requires profound expertise in the physiology and pathophysiology of liver disease. This new edition incorporates the latest information in the field and remains the only available book on the topic. It focuses on the practical aspect of liver anesthesiology and critical care, while providing a comprehensive and in depth summary of the knowledge in this field. Most liver transplant centers now have dedicated teams providing anesthesia care during liver transplantations. In the last years there has been a substantial increase in knowledge and improvement in techniques in anesthesiology and critical care of patients undergoing liver surgery and transplant patients. Liver Anesthesiology and Critical Care Medicine, 2nd Edition includes new chapters on chronic liver failure and hepatic cirrhosis, preoperative risk assessment, evidence in liver anesthesiology, the splanchnic and systemic circulation in liver disease and a special focus on analgesia for liver resection including regional techniques. Written for anesthesiologists and critical care physicians caring for patients undergoing liver surgery and transplantation, this book proves to be an essential companion and review book as the number of liver surgeries with higher complexity continue to increase.